The use of Picture and Sentence Matching to Assess Reading for Students at the Early Stage: A Single Case Study - Rochmah, Noviatul; Muhammad, Ribeh Najib; Asari, Slamet (Jetlal, 2025)
Reading assessment is assessing the students’ competence in understanding ideas in the written form. Reading ability is very difficult to access accurately. The students’ reading level will reflect the level at which that student is able to use reading to accomplish goal. The specific skill in reading should be match in any level of learners. In the beginner level usually the learners responding words and their associating graphic symbol. Assessing reading at the beginner level can be done through picture and sentence matching. In this type of reading test the learners will ask to match the sentence with the picture or match the picture with the sentence. The combination between sentence and pictures arouse the students’ comprehension in recognizing words and words groups, phrase, and simple text. This paper discusses about the use of picture and sentence matching for assessing reading at the beginner level to create the students’ interest in reading skill. Key words: Assessing, reading, early stage, picture and sentence matching